1988
DOI: 10.1042/bj2490645
|View full text |Cite
|
Sign up to set email alerts
|

Use of a selectively permeabilized isolated rat hepatocyte preparation to study changes in the properties of overt carnitine palmitoyltransferase activity in situ

Abstract: 1. A permeabilized isolated rat liver cell preparation was developed to achieve selective permeabilization of the cell membrane to metabolites and to allow the assay of mitochondrial overt carnitine palmitoyltransferase (CPT I) activity in situ. By performing the digitonin-induced permeabilization in the presence of fluoride and bivalent-metal-cation sequestrants, it was possible to demonstrate that the activity of other enzymes, which are regulated by reversible phosphorylation, was preserved during the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 38 publications
(58 reference statements)
3
18
0
Order By: Relevance
“…Membrane intactness is not invariably achieved by different laboratories, and depends on the method of tissue/cell disruption. By contrast, in whole cells, the preferential permeabilization of the plasma membrane is reproducibly achieved using low concentrations of digitonin, by virtue of the much higher content of cholesterol in this membrane than in the ER (25). The subsequent use of a second membrane-permeabilizing agent, namely alamethacin, a poreforming peptide that acts through an entirely different membrane permeabilization mechanism, allowed the discrete quantification of overt and latent DGAT activities in situ in cells without disruption of the native ER structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane intactness is not invariably achieved by different laboratories, and depends on the method of tissue/cell disruption. By contrast, in whole cells, the preferential permeabilization of the plasma membrane is reproducibly achieved using low concentrations of digitonin, by virtue of the much higher content of cholesterol in this membrane than in the ER (25). The subsequent use of a second membrane-permeabilizing agent, namely alamethacin, a poreforming peptide that acts through an entirely different membrane permeabilization mechanism, allowed the discrete quantification of overt and latent DGAT activities in situ in cells without disruption of the native ER structure.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. 25). Importantly, the additional incubation of cells with alamethacin (20 g/ml), which we used after digitonin to permeabilize the ER, did not increase the amount of glycerol 3-phosphate released by a maximally effective concentration (30 g/ml) of digitonin alone (not shown), indicating that the ability of alamethacin to expose mannose-6-phosphatase activity was entirely due to ER permeabilization and not any additional effect it might have on the integrity of the plasma membrane.…”
Section: Overt and Latent Dgat Activities In Microsomes Andmentioning
confidence: 99%
“…Those studies showed that there was no significant effect of glucagon either on the activity of CPT I in the absence of malonyl-CoA or on the sensitivity of the enzyme to malonyl-CoA inhibition. However, the differences in kinetic characteristics of CPT I induced by starvation and diabetes [3][4][5][6] were entirely preserved, irrespective of the previous treatment of the cells [2]. On the basis of similar experiments, Stephens and Harris [7] concluded that glucagon had a small (25 0%) stimulatory effect on CPT I activity, but that it had no effect on malonyl-CoA sensitivity.…”
Section: Introductionmentioning
confidence: 89%
“…The validity of those studies was questioned [2] on the basis that the use of an anti-CPT II antibody to immunoprecipitate the phosphorylated protein invalidated the conclusion that CPT I was phosphorylated. In an attempt to obtain a functional measure of the effects of glucagon on CPT I in isolated hepatocytes, we conducted studies [2] in which cells were first exposed to glucagon and subsequently permeabilized (in the presence of fluoride and EDTA) with low concentrations of digitonin. This protocol was designed to retain mitochondrial integrity (essential for minimization of the contribution of CPT II towards total CPT activity) as well as any changes in phosphorylation state of CPT I, which was measured in the resulting (washed) cell ghosts.…”
Section: Introductionmentioning
confidence: 99%
“…Although carnitine palmitoyl transferase I is also considered an important control of the ketogenic flux in liver, under certain conditions control shifts away from this enzyme to an intramitochondrial control site (3,4). Many groups suggest that this control lies within the pathway from acetyl-CoA to ketonic bodies, the HMG-CoA pathway (5,6).…”
mentioning
confidence: 99%